2020
DOI: 10.3390/min10121065
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Manganese Sorption on Ukrainian Tuff and Basalt—Order and Diffusion Models Analysis

Abstract: The study aimed to determine the nature of the kinetics of the manganese sorption process on Ukrainian tuff and basalt at different temperatures characteristic of the natural water environment. The scope of the research included manganese sorption kinetic test on natural mineral sorbents at temperatures of 10, 17.5 and 25 °C in slightly acidic conditions. Sorption (pseudo-first order, pseudo-second order and Elovich models) and diffusion kinetic models (liquid film diffusion and intraparticle diffusion) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…It should be noted that in the presented study, the temperature was much lower than in other studies, since the groundwater temperature was simulated. Our previous study indicated that the Mn adsorption rate and removal efficiency do not change at temperature 10-25°C [Reczek et al 2020]. However, differences in experimental conditions and material preparation may be the reason for obtaining lower adsorption capacity of the Sokirnitskoe zeolite (clinoptilolite) than in paper of Korablew et al [2017].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It should be noted that in the presented study, the temperature was much lower than in other studies, since the groundwater temperature was simulated. Our previous study indicated that the Mn adsorption rate and removal efficiency do not change at temperature 10-25°C [Reczek et al 2020]. However, differences in experimental conditions and material preparation may be the reason for obtaining lower adsorption capacity of the Sokirnitskoe zeolite (clinoptilolite) than in paper of Korablew et al [2017].…”
Section: Resultsmentioning
confidence: 98%
“…However, it can be generalized that at slightly acidic pH, close to neutral, the removal of manganese on volcanic tuff and basalt gives good results. Although the pH of the solution was below pH PZC of the materials (volcanic tuff pH PZC =8.9 and basalt pH PZC =8.5) Mn removal is not inhibited by electrostatic repulsion[Reczek et al 2020].Basalt has the highest affinity for Mn represented by the lowest value of the Langmuir's b parameter. Importantly, increasing the concentration of tuff and zeolite from 1g/1L to 2g/1L decreased its affinity for Mn, represented by higher b values.…”
mentioning
confidence: 92%
“…Table 3 shows the intercept C ≠ 0, it indicates curves fitted by the intraparticle diffusion model does not pass through the origin and there is a boundary layer control effect in the adsorption process. Intraparticle diffusion is not the only control step of the adsorption rate in the adsorption reaction, liquid film diffusion is also involved in controlling the adsorption process simultaneously (Reczek et al 2020). The correlation coefficient of the liquid film diffusion model was greater than that of the intraparticle diffusion model, indicating that the control of adsorption rate by liquid film diffusion was greater than that by intraparticle diffusion.…”
Section: Kinetic Adsorption Characteristicsmentioning
confidence: 95%
“…Plante et al [17] demonstrated that plagioclase controlled Ni mobility through sorption in waste rock piles of the Tio mine. More recently, Reczek et al [104] and Trach et al [105] stated that volcanic tuff and basalt effectively adsorb Mn. Therefore, the next step of the geochemical assessment of Akasaba West materials should involve sorption experiments to investigate the effect of the sorption capacity of plagioclase on water quality.…”
Section: Model Benchmarking (I) D1 Weathering Cellmentioning
confidence: 99%